Covariação morfossintática no português brasileiro: identificação dialetal de estudantes da Universidade Federal de Sergipe - Silva, Jose Manoel Siqueira da (2025)
Dialectal varieties are formed by a set of linguistic features at different language levels, making them distinct from other varieties (Chambers; Trudgill, 2004; Mansfield; Leslie- O’neill; Li, 2023). Studies on dialectal varieties of Brazilian Portuguese (BP) have focused on describing patterns of variable phenomena in isolation. While this approach has allowed for a deeper understanding of the behavior of variable rules and their effects on the organization of the language, on the other hand, there is little knowledge of the interaction between different linguistic variables – covariation (Guy, 2013; Oushiro, 2015a; 2016a; Beaman, 2022; Freitag, 2022). Even among covariation approaches, the focus on phenomena has prioritized the phonetic-phonological level (Labov, 2006[1966]; Tamminga, 2019). Assuming that covariation analysis is relevant for identifying the dialectal origin of speakers, and that expanding it to morphosyntactic variables can help reveal recurring patterns of language use in specific geographic regions, which can be verified empirically, in this work we investigate the following question: does the description of morphosyntactic covariation in the speech of groups of speakers from different geographic regions identify their dialectal origin? We explore the hypothesis that the identification of the dialectal origin of the speaker from morphosyntactic variables can be performed using covariation analysis techniques. Thus, our goal is to describe covariation between four geographically distinct morphosyntactic variables of BP: i) variable use of the definite article before prenominal possessives (sua casa x a sua casa) (ART); ii) second-person singular personal pronouns (2PS) as a function of subject (tu anda x você anda x cê anda) (pro2PS); iii) 2PS clitic pronouns (te vi x lhe vi) (cli2PS); and iv) 2PS possessive pronouns (tua casa x sua casa) (pos2PS). We used covariation analysis techniques to identify dialectal patterns, such as correlation tests, social grouping patterns, and cluster analysis. The data used come from sociolinguistic samples with the speech of 181 university students from the Federal University of Sergipe (UFS) – Deslocamentos (2019), Deslocamentos (2020), and Linguagem Corporificada (2023) – considering the social variables displacement, time in the course, and gender of the speaker. In the individual analyses, the results show the predominance of the absence of an article before possessives, of the pronoun você as the subject, of the clitic te, and of the possessive seu. Social variables, such as displacement, time in the course, and gender, correlate with the morphosyntactic variables. Covariation analysis revealed significant correlations between the pairs ART~pro2PS, pro2PS~pos2PS, cli2PS~pos2PS, and pro2PS~cli2PS, as well as a pattern of social clustering in which more than 30% of speakers from cetain groups share similar frequencies. The cluster analysis identified three natural groupings based on linguistic uses, considering similarities and differences. Although covariation techniques revealed relevant patterns, the identification of the dialectal origin of the speakers was only possible in cluster analysis, in which speakers from Bahia presented distinct behavior from other speakers. Despite limitations, such as the low frequency of morphosyntactic variables in the collected data, this study contributes methodologically to the description of covariation patterns and reinforces the importance of covariation studies for the characterization of dialectal patterns.